농식품 안전성 조사 효율성 제고를 위한 시스템 구축 - 이계임 (한국농촌경제연구원, 2008)
In Korea, National Agricultural Products Quality Management Service (NAQS) has conducted food safety inspection programs about agricultural products after 1996, and the number of items and samples inspected by NAQS in 2007 were 150 items and 68 thousand samples, respectively. Even though NAQS keeps endeavoring to increase the level of food safety of agricultural products, the current inspection system still has several problems including following: unclear standards to decide the numbers of samples and farmers' resistance about sampling in field. The main goal of this research is to analyze the inspection programs of NAQS and to suggest the more efficient food safety inspection system about agricultural products. Survey analyses and interviews were conducted to analyse the current status of inspection programs of NAQS, and the case studies about the food safety inspection system of U.S, Australia, EU, Japan, and Taiwan were performed to deduce the implications. The research also developed the method to derive the minimal numbers of samples for inspection, which is statistically reliable. The research showcases the basic strategies for the efficient management of food safety inspection programs of NAQS as follows: first, strengthening of functions for inspection before the stage of selling agricultural products, second, integration of management system for food safety inspection, third, establishment of inspection system at the national level, forth, Improvement of methods for inspection, fifth, clear sharing of roles between central government and local governments. Basically, discussion and suggestions in this paper will offer the guidelines to increase the level of efficiency of food safety inspection of NAQS. Researchers: Kyei-Im Lee, Ji-Hyeon Choi, Sounghun Kim and Eun-Young Son Research period: 2008. 8 ~ 12 E-mail address: lkilki@krei.re.kr